Port State Measures To Combat Illegal, Unreported, and Unregulated Fishing On The High Seas - Saadillah, Maulida Hadry (Mahadi: Indonesia Journal of Law, 2023)
IUU fishing on the high seas is a serious problem for the conservation and management of the resource of high seas fisheries. There is no statistic that can adequately explain the ecological impacts of overfishing because of IUU fishing and its effect on biodiversity. Port states play a pivotal role in preventing IUU caught fish from entering the local and international trade markets. Port state control may be a deterrent to IUU operators since it would force them to call into more remote ports with less strict port state measures, therefore increasing the cost of operations for them. Thus, it can be said that port state measures are an effective means of preventing IUU high seas caught fish from being delivered to the consumer.